Diagnostic value of Beep and Yo-Yo tests in assessing physical performance of female soccer players - Gabrys, T.; Stec, K.; Michalski, C.; Pilis, W.; Pilis, K.; Witkowski, Z. (Biomedical Human Kinetics, 2019)
Study aim: The aim of the present study was to compare the physiological responses of female soccer players recorded during the Beep Test and Yo-Yo Test. Material and methods: Twenty.three high-level women's soccer players underwent aerobic fitness testing. Modification of the Beep Test consisted of: lengthening the distance between turns to 40 m, extending the time between the increase in speed, and including a rest period between exercise stages. During the running efforts the length of the distance run in both tests was measured as well as circulatory and respiratory variables. For statistical analyses only data obtained at maximum loads in both tests were accepted. Results: Analyzed variables showed that all values recorded in both tests reached maximum values and did not differ statistically significantly. Conclusion: The results show that both applied tests loaded the soccer players to a similar maximum degree and the tests are suitable for assessing the aerobic physical performance.